GAMBARAN ETOS KERJA PADA PEDAGANG ETNIS TIONGHOA DI JAKARTA - Stefanus Reinhard (Psibernetika, 2014)
The purpose of this study was to see an overview of the work ethic of ethnic Chinese traders, this is due to a reflection of a good work ethic through the inherent characteristics of the ethnic Chinese merchants like never give up, work hard, able to delay gratification, and simplicity. The research method used in this research is descriptive quantitative and perform calculations using SPSS 19.0 for windows. Descriptive analysis of the results of frequency on the attached table data, was found that the work ethic of ethnic Chinese traders in the category are likely to be low. this is due to other factors that affect the lifestyle, generational differences, type of work, and the influence of the results of the process of assimilation. The questionnaire used is the Multidimensional Work Ethic Profile - Short Form (SF - MWEP) (Meriac et al., 2013). Thus the hypothesis of the study, which reported an overview of a high work ethic on ethnic Chinese merchants in Jakarta is rejected. Keywords: Ethnic Chinese, Work Ethic, Traders